Derive e macchinazioni mitologiche. Omaggio a Furio Jesi (Itinera, 2015)
The expression “mythological machine” indicates for Furio Jesi a complex autopoietic apparatus which incorporates and transfers collective experiences together with the socialized knowledge of myth, while it reproduces, with political purposes, mythologies, tales, narrations and artistic figurations. “Mythological materials” are products historically-verifiable by the machine, whereas the “myth” is the invention of something to whose autonomous existence the machine alludes. The science of mythology is the study of the internal mechanisms of the mythological machine, the analysis of the inner and autonomous existence linguistic circulation that makes those materials mythological. The science of myth is instead the typical science of what historically does not exist which is therefore translatable in the analysis of the different modalities  of the myth.